PENGARUH KUALITAS LAYANAN DAN IMAGE TERHADAP LOYALITAS PENUMPANG JASA JOUMPA DI BANDARA I GUSTI NGURAH RAI - Lallo Pasapan, Theresya; Sudana, I Putu; Suwena, I Ketut (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024), 2024)
This study examines the effect of service quality and image on the loyalty of Joumpa service passengers at I Gusti Ngurah Rai Airport. Services are perceived as having good quality if they can meet or even exceed their expectations. Consumer perceptions of service quality can be influenced by several factors, one of which is brand image. Especially at the airport, many tourists come and go to their respective domestic flight destinations. Joumpa provides VIP Assistance services to all passengers who have made reservations in advance. In this study using a sampling technique that has collected 100 samples, consisting of domestic passengers using joumpa services. The data-gathering techniques in this study use library studies, observation, interviews, and questionnaires. Then the data analysis technique in this study is the quantitative analysis using the SPSS program (version 29) to see how the quality of the service and image affects passenger loyalty. The study suggests the quality of services has had a significant impact on passenger loyalty. Then the variable image is partial to no positive and significant effect on passenger loyalty.